Synthesis, structure and computer bioprognosis new hydrazons based on hydrosides o- and p-hydroxybenzoic acids - Nurkenov, О.А.; Satpaeva, Zh.B.; Fazylov, S.D.; Turdybekov, К.М.; Seilkhanov, Т.М.; Suleimen, Ye.М.; Iskakova, Zh.B. (KSU Publ., 2017)
Interaction of hydrazides of o- and p-hydroxybenzoic acids with substituted aromatic aldehydes yielded the corresponding hydrazone derivatives. Using the computer program PASS, a bioproject of N-arylidene hydrazones was carried out and it was shown that their expected activity combines both the physiological activity of the initial hydrazides of o- and p-hydroxybenzoic acids and the constituent components of the structural molecule. The structures of the synthesized compounds were studied by 1H NMR and 13C NMR spectroscopy, as well as with the data of the two-dimensional spectra COSY (1H-1H) and HMQC (1H-13C). The values of chemical shifts, multiplicity and integrated intensity of the 1H and 13C signals in one-dimensional NMR spectra are determined. Homogeneous and heteronuclear interactions are established using spectra in the formats COSY (1H-1H) and HMQC (1H-13C), confirming the structure of the compounds under study. X-ray diffraction study of N-(5-bromo-2-hydroxybenzylidene)-4-hydroxybenzohydrazide, whose molecule is bound by a hydrogen bond to an ethanol solvate molecule.
о- жəне п-гидроксибензой қышқылдары негізіндегі жаңа гидразондардың синтезі, құрылымы мен компьютерлік биоболжам
Синтез, строение и компьютерный биопрогноз новых гидразонов на основе гидразидов о- и п-гидроксибензойных кислот
Keywords: o- and p-hydroxybenzoic acid hydrazide; hydrazone; aromatic aldehydes; NMR spectroscopy